Behçet’s Disease - A Rare Form of Small Vessel Vasculitis (Journal of Medicine, 2023)
Behçet’s disease is a rare vasculitis of unknown aetiology though there is a strong genetic association with HLA-B51 characteristically targets small arteries and venules. Multiple deep oral ulcer and genital ulcer is a common presentation. Ocular involvement is also commonly occurs in the form of anterior or posterior uveitis or retinal vasculitis. Neurological manifestation occurs in the form of brainstem or pyramidal tract symptom. Thrombosis can occur but renal involvement is unlikely. Our patient Mrs X, 47 year old has been suffering from recurrent episode of oral ulcer, genital ulcer, redness of eye and dysphagia for the last 12 years. T here was relapse and remission of the symptoms. Her Ophthalmoscopic examination was normal. Upper GI endoscopy revealed multiple esophageal ulcers. ANA, Anti CCP, cANCA, pANCA, HSV 1&2- IgM, CMV- IgM, TPHA, Anti -HIV 1&2 were negative. She was treated with oral steroid and azathioprine and all the lesions resolved completely.J MEDICINE 2023; 24: 56-58